KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA MENGGUNAKAN KURIKULUM MERDEKA DITINJAU DARI GAYA BELAJAR - Agustiaman; Jamilah; Abdillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the critical thinking skills of students in class VIII A at SMP Sungai Kehidupan Pinoh Selatan in terms of their learning styles. This research is qualitative and uses a descriptive approach. The subjects of this study are the students of class VIII A at SMP Sungai Kehidupan Pinoh Selatan. The subjects analyzed and interviewed consist of 6 students based on their learning styles, namely visual, auditory, and kinesthetic. The subjects were selected using purposive sampling techniques. The instruments used for data collection include tests to measure students' critical thinking skills and questionnaires to determine students' learning styles. Based on the findings obtained in this study, it can be concluded that the learning styles of students—visual, auditory, and kinesthetic—affect their learning outcomes, particularly in critical thinking skills. Students with high critical thinking skills are able to meet the indicators, while students with low critical thinking skills have not yet met the indicators.